Structured robust control for a Pmdc motor speed controller using swarm optimization and mixed sensitivity approach - Kaitwanidvilai, Somyot; Ngamroo, Issarachai (My University, 2010)
This paper proposes a new technique for designing a robust DC motor speed controller based on the concepts of fixed-structure robust controller and a mixed sensitivity method. Performance is specified by selecting the closed-loop objective weight, and uncertainties caused by the parameter changes of motor resistance, motor inductance and load are used to formulate the multiplicative uncertainty weight. Particle Swarm Optimization (PSO) is adopted to solve the optimization problem and find the optimal structured controller. The proposed technique can solve the problem of complicated and high order controller of conventional full order H ∞ controller and also retains the robust performance of conventional H ∞ optimal control. The performance and robustness of the proposed speed controller are investigated in a Permanent Magnet DC (PMDC) motor in comparison with the controllers designed by conventional H ∞ optimal control and conventional ISE method. Results of simulations demonstrate the advantages of the proposed controller in terms of simple structure and robustness against plant perturbations and disturbances. Experiments are performed to verify the effectiveness of the proposed technique. © Springer Science+Business Media B.V. 2010.
Keywords: H ∞ optimal control; Particle swarm optimization; PMDC motor speed control